1996
DOI: 10.1111/1540-5885.1350422
|View full text |Cite
|
Sign up to set email alerts
|

What Separates Japanese New Product Winners from Losers

Abstract: Operating in the upper echelons of highly competitive, global markets, numerous Japanese firms enjoy well‐deserved reputations for excellence in new product development. Despite this success, however, almost no research has been conducted to explore the keys to successful new product development in Japanese companies. For the most part, research in this area has focused on North American and European firms. X. Michael Song and Mark E. Parry address this gap with a study of 404 Japanese firms and 788 new produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
2
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 49 publications
4
123
2
3
Order By: Relevance
“…On the basis of the feedback from these two panels of experts and a second round of group interviews, we prepared a draft questionnaire including the items judged to have high consistency and face validity with the constructs. We used two parallel double translations to translate the questionnaire into Japanese (for details, see Song and Parry [1996]). The final stage of measurement development consisted of two pretests of the resulting questionnaires with representative respondents to identify wording problems or ambiguities.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the feedback from these two panels of experts and a second round of group interviews, we prepared a draft questionnaire including the items judged to have high consistency and face validity with the constructs. We used two parallel double translations to translate the questionnaire into Japanese (for details, see Song and Parry [1996]). The final stage of measurement development consisted of two pretests of the resulting questionnaires with representative respondents to identify wording problems or ambiguities.…”
Section: Methodsmentioning
confidence: 99%
“…Japanese firms have achieved domination in many industries, both those characterized by low technology and those characterized by high technology (Kodama, 1995; Takeuchi & Nonaka, 1986). In addition, some past research has suggested that the Japanese NPD process is highly adaptive and responsive to the perceived external environment (Clark & Fujimoto, 1991;Song & Parry, 1996, 1997b, 1999. Thus,…”
mentioning
confidence: 99%
“…In the last 20 years, many studies have identified the critical success activities during the development process for new manufactured products (Cooper, 1979;Cooper and Kleinschmidt, 1986;Parry and Song, 1994;Song and Parry, 1996;Atuahene-Gima, 1996), as well as services (Cooper and de Brentani, 1991;de Brentani and Cooper, 1992;de Brentani, 1993;Edgett and Parkinson, 1994;Edgett, 1996;Deal and Edgett, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Song and Parry (1994) report a positive correlation between proficiency in market research and launch activities and new product performance. Interestingly, researchers were able to replicate these results in China (Parry & Song, 1994); Japan (Song & Parry, 1996); and Australia (Dwyer & Mellor, 1991). More evidence for the positive impact of launch proficiency on new product performance has been provided by, for example, Hultink et al (1998) and Langerak et al (2004).…”
Section: Journal Of Global Scholars Of Marketing Science 297mentioning
confidence: 93%